Etnografi Dakwah Ulama Rantau pada Etnis Dayak Ngaju di Kalimantan Tengah - Anwari, Rizki Amalia Nur; Pawito, Pawito; Purwasito, Andrik (Departement of Islami Comuunication and Broadcasting, Faculty of Da'wah and Communication, State Islamic University of Sunan Ampel (UINSA) Surabaya Indonesia, 2018)
This study aims to look at the role of ulama rantau in the process of proselytising (da'wah) in the Ngaju Dayak community, East Kotawaringin town, Central Kalimantan Province, particularly regarding the way ulama deal with a Dayak local culture which deeply remains lived within this community. Using a qualitative research method and the ethnographic approach, the findings revealed that the way ulama rantau conveyed the da'wah messages in a polite manner implicated to Ngaju Dayak ethnic society's acceptance towards Islam. Further, because ulama rantau respected the local cultural wisdom when conveying da’wah, people appreciated Islam brought by ulama (da’i) n the midst of a society which has different beliefs and cultural backgrounds.